Determining the maximum sediment dispersion in an ocean disposal site for dredged material in Buenaventura, Colombia - Villadiego Rojas, Leydis; Daza González, Ricardo; Salcedo Castilla, Bladimir (International Journal of Engineering and Technology, 2020)
This paper presents an analysis of the affected area at an ocean disposal site, in terms of sediment dispersion, as a consequence of the dis-posal of dredged material from the approach channel for Buenaventura´s Port. The analysis was carried out at three points within Buenaven-tura´s Bay, one located at the authorized disposal site, a second point at a proposed future disposal site and a third point at the Bocana Sector, where the highest tidal velocities are identified. The PTM (Particle Tracking Model) mathematical model was used for this investigation, showing that due to the hydrodynamic conditions, a sediment particle can reach a longer dispersion distance from its original disposal point. Finally, sediment dispersion at the three analysis points were compared in terms of current velocity and maximum displacement.